2015
DOI: 10.1002/nag.2424
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of railway ballast at the particle scale

Abstract: Summary The paper describes the development of a technique to simulate triaxial tests on specimens of railway ballast numerically at the particle scale and its validation with reference to physical test data. The ballast particles were modelled using potential particles and the well‐known discrete element method. The shapes of these elemental particles, the particle size distribution and the number of particles (N = 2800) in each numerical triaxial specimen all matched closely to the real ballast material bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 32 publications
0
62
0
Order By: Relevance
“…Ahmed et al [2] presented discrete element simulations of railway ballast that showed close agreement with monotonic laboratory triaxial tests carried out by Aingaran [3], on onethird scale ballast. The experimental test rig is shown in Fig.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Ahmed et al [2] presented discrete element simulations of railway ballast that showed close agreement with monotonic laboratory triaxial tests carried out by Aingaran [3], on onethird scale ballast. The experimental test rig is shown in Fig.…”
Section: Introductionmentioning
confidence: 58%
“…It was shown not to be possible to match the laboratory behaviour using the standard Hertzian elastic contact law with an elastic-perfectly plastic tangential slip model, presented in [2]. This suggests that some damage must be occurring at particle contacts.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations